Admissions for ambulatory care sensitive conditions on rural islands and their association with patient experience: a multicentred prospective cohort study - Makoto Kaneko; Takuya Aoki; Masafumi Funato; Keita Yamashiro; Kaku Kuroda; Moe Kuroda; Yusuke Saishoji; Tatsuya Sakai; Syo Yonaha; Kazuhisa Motomura; Machiko Inoue (BMJ Open)
Objectives The rate of admissions for ambulatory care sensitive conditions (ACSCs) is a key outcome indicator for primary care, and patient experience (PX) is a crucial process indicator. Studies have reported higher rates of admission for ACSCs in rural areas than in urban areas. Whether there is an association between admissions for ACSCs and PX in rural areas has not been examined. This study aimed to document admissions for ACSCs on Japanese rural islands, and assess whether there was an association between the rate of admissions for ACSCs and PX.Design Multicentred, prospective, cohort studySetting This study was conducted on five rural islands in Okinawa, Japan.Participants The study participants were all island inhabitants aged 65 years or older.Primary outcome measures This study examined the association between ACSCs and PX assessed by a questionnaire, the Japanese Version of Primary Care Assessment Tool. ACSCs were classified using the International Classification of Diseases, Tenth Revision, and the rate of admissions for ACSCs in 1 year.Results Of 1258 residents, 740 completed the questionnaire. This study documented 38 admissions for ACSCs (29 patients, males/females: 15/14, median age 81.9) that included congestive heart failure (11), pneumonia (7) and influenza (5). After adjusting for covariates and geographical clustering, admissions for ACSCs had a significant positive association with each patient’s PX scores (OR per 1 SD increase=1.62, 95% CI 1.02–2.61).Conclusions Physicians serving rural areas need to stress the importance of preventive interventions for heart failure, pneumonia and influenza to reduce the number of admissions for ACSCs. Contrary to previous studies, our findings might be explained by close patient–doctor relationships on the rural islands.